The Effects of Foreign Ownership in Africa : Evidence from Ghana, Kenya and Zimbabwe - World Bank (Washington, DC, 2012)
The effect of foreign ownership in Africa is based on an analysis of survey data of firms in Zimbabwe, Ghana, and Kenya compiled by the Regional program on Enterprise Development (RPED). This study attempts to show the relationship between foreign ownership and firm-level value added in Sub-Saharan Africa. The study finds a clear indication that majority foreign ownership has a positive influence on value added. The study looks at whether or not firms with any foreign equity have higher value added. It also looks at whether majority foreign ownership is correlated with value added. The study includes other factors that determine firm productivity, such as worker training programs, quantities of labor and capital, and the education of the general manager, in order to control for other factors that influence firm performance.